# Write the general formula for following alternating series in the form ?

### 1 Answer

Relevance

- Wayne DeguManLv 72 months ago
The nth term is 3/(n + 1)

However, the terms alternate between positive and negative values.

odd numbered terms are positive and even are negative

i.e. (-1)ⁿ⁺¹...so, even values of n makes n + 1 odd

=> -1 raised to an odd power = -1

so, 3(-1)ⁿ⁺¹/(n + 1)

Checking with n = 4 gives:

3(-1)⁵/5 => -3/5

Hence, ∑ 3(-1)ⁿ⁺¹/(n + 1) => 3∑(-1)ⁿ⁺¹/(n + 1)

:)>

Still have questions? Get answers by asking now.